Development of an Electronic Contextual PJBL Worksheet for Simple Machine Analysis in Oil Palm Harvesting Movements - Nugroho, Agung Nur; Nurohman, Sabar; Wiyatmo, Yusman (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
The utilization of the surrounding environment as a source of science learning, particularly in oil palm plantation areas, has not yet been optimally implemented. One learning medium that enables students to interact directly with their environment is a contextual Project-Based Learning (PJBL) electronic worksheet. This study aims to develop a contextual-based electronic PJBL worksheet for analyzing simple machine principles in the human skeletal system during oil palm harvesting activities. The development procedure followed the research and development model proposed by Richey and Klein. Limited testing was conducted with ninth-grade students at SMP Evans Indonesia using questionnaires and group interviews to obtain student responses to the developed worksheet. The results indicate that the overall student response to the electronic worksheet falls within the very good category. Nevertheless, several suggestions were provided by students to improve technical features and enhance learning comfort, which were used as considerations for product refinement.